2013
DOI: 10.1097/prs.0b013e3182729cfc
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age on Human Adipose-Derived Stem Cells

Abstract: Adipose-derived mesenchymal stem cells are available across all age groups. Infant-derived cells are morphologically spindle-shaped, with long telomeres, and exhibit enhanced angiogenic and osteogenic capabilities compared with older cells. Conversely, all age groups exhibit similar osteogenic paracrine activity, and the authors posit that clinical applicability is conserved during the adult to elderly period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
80
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 35 publications
4
80
0
2
Order By: Relevance
“…Results presented in this study and elsewhere suggest that thymus MSCs may be a promising candidate for therapeutic use [6,7]. Given the low expression human leukocyte antigen class I on a subset of neonatal human thymus MSCs, as shown in this study and elsewhere [7,70], use of these MSCs may also yield advantages in the allogeneic setting (e.g., use in older patients with ischemic heart disease), in which it is more likely to complement the advantages of neonatal MSCs over adult MSCs [71][72][73]. However, improvements in isolation yield are needed to make clinical use of thymus MSCs feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Results presented in this study and elsewhere suggest that thymus MSCs may be a promising candidate for therapeutic use [6,7]. Given the low expression human leukocyte antigen class I on a subset of neonatal human thymus MSCs, as shown in this study and elsewhere [7,70], use of these MSCs may also yield advantages in the allogeneic setting (e.g., use in older patients with ischemic heart disease), in which it is more likely to complement the advantages of neonatal MSCs over adult MSCs [71][72][73]. However, improvements in isolation yield are needed to make clinical use of thymus MSCs feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas bone marrow has been shown to be a source of stem cells, it is particularly important to consider the use of adipose-derived mesenchymal stem cells (AD-MSCs) due to their ease of isolation and abundance. Whereas there have been studies noting various changes in AD-MSC properties with aging [74][75][76]78,79,82,83,85 and diabetes, 71 it is unclear how donor demographics affect functions related to vascular engineering such as the ability to secrete factors to induce SMC migration and their potential to differentiate into SMCs. Also, investigating if donor demographics alter the factors secreted by AD-MSCs will have a broad impact as the AD-MSC secretome has been used for a variety of applications.…”
Section: Introductionmentioning
confidence: 99%
“…While taken together, these studies have shown that cellularizing tissue-engineered grafts significantly improves the patency and regeneration over their acellular counterparts; these models hold limited relevance for clinical translation since in practice, cells would need to be harvested from patients at high cardiovascular risk such as diabetics 64,65 and the elderly. [66][67][68] In addition, these high-risk groups possess pathologic conditions such as a hyperglycemic environment [69][70][71][72] and ageassociated senescence, [73][74][75][76][77][78][79][80][81][82][83][84][85] respectively, which can decrease the ability of their stem cells to proliferate, differentiate into specific mesenchymal cell types, and promote angiogenesis. Whereas bone marrow has been shown to be a source of stem cells, it is particularly important to consider the use of adipose-derived mesenchymal stem cells (AD-MSCs) due to their ease of isolation and abundance.…”
Section: Introductionmentioning
confidence: 99%
“…The inter-subject variability inevitably influences the evaluation of cellular osteogenic potential due to differences in age, physiologic and hormonal state, and health conditions and gender of the donors. 9,10 Therefore, the ideal experimental scenario would assess osteogenic differentiation of MCs obtained from different tissues in the same donor. Then, a direct comparison can be performed to assess ACs and BMCs under the same conditions, with an emphasis on optimized bone formation.…”
Section: Introductionmentioning
confidence: 99%